The Impact of the Antibiotic Fosfomycin on Wastewater Communities Measured by Flow Cytometry - Li, Shuang; Liu, Zishu; Süring, Christine; Chen, Luyao; Müller, Susann; Zeng, Ping (Frontiers in Microbiology, 2022)
Fosfomycin is a re-emergent antibiotic known to be effective against severe bacterial infections even when other antibiotics fail. To avoid overuse and thus the risk of new antibiotic resistance, the European Commission has recommended the intravenous use of fosfomycin only when other antibiotic treatments fail (EMA, 2020). A release of fosfomycin into the environment via wastewater from municipalities, but also already from the producing pharmaceutical industry, can seriously undermine a sustaining therapeutic value. We showed in long-term continuous-mode bioreactor cultivation and by using microbial community flow cytometry, microbial community ecology tools, and cell sorting that the micro-pollutant altered the bacterial wastewater community (WWC) composition within only a few generations. Under these conditions, fosfomycin was not readily degraded both at lower and higher concentrations. At the same time operational reactor parameters and typical diversity parameters such as α- and intra-community β-diversity did not point to systems changes. Nevertheless, an intrinsic compositional change occurred, caused by a turnover process in which higher concentrations of fosfomycin selected for organisms known to frequently harbor antibiotic resistance genes. A gfp-labelled Pseudomonas putida strain, used as model organism, and a possible future chassis for fosfomycin degradation pathways was augmented and outcompeted in all tested situations. The results suggest that WWCs, as complex communities, may tolerate fosfomycin for a time, but selection for cell types that may develop resistance is very likely. The approach presented allows very rapid assessment and visualization of the impact of antibiotics on natural or managed microbial communities in general and on individual members of these communities in particular.